THE CAREER SELF-EFFICACY TRAINING TOWARDS INCREASING CAREER MATURITY OF SLOW LEARNER STUDENTS - Ekanesia, Pratidina (Journal of Business and Management Inaba, 2022)
Every student has their own potential, and those with special needs are not an exception. One of them are the slow learners. They need to have a chance to compete in the career world and reach career maturity. However, some students are uncertain in deciding a career path that goes along with their ability and major. This study is aimed to test the effect of Career Self Efficacy training to career maturity improvement of 12th grade slow learner students in SMK X Bandung. This study uses a population sampling technique in which subjects’ characteristics are defined by their IQ, low level in career maturity and parents’ consent. From there, it is found that there are four slow learners majoring in culinary in 12th grade. In this study, single-group pretest-posttest design is used to measure change in career maturity after the Career Self Efficacy training. Wilcoxon sign-rank shows a significant improvement after the subjects participated in the training. Based on the result, it is suggested for school to make Self Efficacy training as a career counseling program for slow learner students.